Building Resilient Renewable Infrastructure in an Era of Climate and Market Volatility - Mofeoluwa Oyekan; Emmanuel Igba; Shereef Olayinka Jinadu (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
The accelerating impacts of climate change and increasing market volatility pose significant challenges to the development and sustainability of renewable energy infrastructure. Building resilient systems requires not only technological innovation but also adaptive strategies that address environmental, economic, and policy uncertainties. This review examines the multidimensional approaches necessary for enhancing resilience in renewable infrastructure, including climate risk assessment, integration of energy storage and smart grid technologies, diversification of energy portfolios, and the role of policy frameworks in fostering stability. It also explores how market dynamics, such as fluctuating commodity prices, geopolitical risks, and evolving demand patterns, influence infrastructure investment and long-term viability. By analyzing case studies, best practices, and emerging trends, the paper highlights pathways for strengthening the adaptability and robustness of renewable systems. Ultimately, this review underscores the importance of resilience as a foundational principle in ensuring reliable, sustainable, and economically viable renewable energy infrastructure in an era marked by uncertainty and rapid transformation.